Experimental study on investigation of dynamics of hexapod robot for mobile machining. Issue 5 (May 2016) - Tunc, Lutfi; Shaw, Jay
Abstract Mobile machining with industrial robots is proposed to be a cost-effective and portable alternative to large-scale CNC machine tools in machining of large-scale parts designed in aerospace, nuclear manufacturing and energy industries. Although robotic machining offers several potential advantages, it is also subject to major technical challenges. In this paper, the dynamics of a hexapod platform utilized for robotic milling is investigated in terms of rigidity, position-dependent dynamics and cross compliance caused by the complex kinematic chain. Considering the dynamic flexibility of the robotic platform, its effects on tool-tip dynamics are examined. The effect of the robot position relative to the workpiece on the dominant modes observed in transfer functions is discussed, which may be further used to locate the robot to attain better stability depending on the case. The dynamic responses at the moving platform and at the tool tip are measured through tap tests. Although the paper does not focus on modelling, the results can be generalized to mobile machining with hexapod robots.